Evolução cromossômica em crocodylia (Animalia, Reptilia) - Oliveira, Vanessa Cristina Sales (2024)
Crocodylia is an order that has undergone very few morphophysiological, biogeographic and genetic changes over time, despite having originated between the end of the Triassic and the beginning of the Jurassic, approximately 200 million years ago. This order is divided into three families: Crocodylidae, Gavialidae, and Alligatoridae, with representatives distributed on practically all continents, except for Europe and Antarctica, thus being geographically delimited by temperature. According to phylogenetic studies, crocodilians form a monophyletic group together with dinosaurs, pterosaurs, and birds, therefore suggesting a closer relationship with birds than with the rest of Archosauria. Despite this proximity, the fact that both taxa have a certain karyotypic variability and the importance of having access to these data to better understand the evolutionary history of these animals, studies on cytogenomic characterization in reptiles and especially in crocodilians, are still quite outdated, following a completely different path from its sister group. Therefore, this thesis presents the analyzes carried out with different cytogenomic techniques on representative species of two of the three families – Alligatoridae and Crocodylidae – to enable a better understanding of the processes involved in the genomic and chromosomal evolution of their species. We characterize for the first time cytogenetic and molecular data for all Alligatoridae species, observing a notable chromosomal conservatism among Caimaninae species, consistent with the dichotomy observed between the Caimaninae and Alligatorinae subfamilies, and demonstrate the role of rearrangements in the evolutionary history of these species. The Crocodylidae data demonstrate that despite not being as conserved as alligators, they have a karyotype closer to the ancestral karyotype of Crocodylia than other families, and showed how rearrangements are involved in the changes that gave rise to the current diversity of karyotypes in crocodilians.